To find the point-slope equation using the two points (3, 34) and (10, 62), we first need to calculate the slope (m) of the line between these two points using the formula:
\[ m = \frac{y_2 - y_1}{x_2 - x_1} \]
Substituting the given points:
\[ m = \frac{62 - 34}{10 - 3} = \frac{28}{7} = 4 \]
Now that we have the slope (m = 4), we can use the point-slope form of the equation, which is:
\[ y - y_1 = m(x - x_1) \]
We can use either of the two points, but let’s use the point (3, 34):
\[ y - 34 = 4(x - 3) \]
Thus, the point-slope equation is:
\[ (y - 34) = 4 (x - 3) \]
Therefore, the correct response is:
(y - 34) = 4 (x - 3)